2018
DOI: 10.1007/s12011-018-1501-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Safety and Pharmacokinetic Evaluation of Three Oral Selenium Compounds in Cancer Patients

Abstract: Selenium (Se) compounds have demonstrated anticancer properties in both preclinical and clinical studies, with particular promise in combination therapy where the optimal form and dose of selenium has yet to be established. In a phase I randomised double-blinded study, the safety, tolerability and pharmacokinetic (PK) profiles of sodium selenite (SS), Se-methylselenocysteine (MSC) and seleno-l-methionine (SLM) were compared in patients with chronic lymphocytic leukaemia and a cohort of patients with solid mali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…It is possible that higher doses of Se might safely be used with some chemotherapy drugs. It is noteworthy that dosing to achieve plasma Se levels determined by this in vitro study would not apply to seleno-l-methionine, as it is non-specifically incorporated into the general protein pool, especially albumin, which gives disproportionately high plasma Se levels compared to dosing with equivalent elemental Se doses of sodium selenite or Se-methylselenocysteine [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that higher doses of Se might safely be used with some chemotherapy drugs. It is noteworthy that dosing to achieve plasma Se levels determined by this in vitro study would not apply to seleno-l-methionine, as it is non-specifically incorporated into the general protein pool, especially albumin, which gives disproportionately high plasma Se levels compared to dosing with equivalent elemental Se doses of sodium selenite or Se-methylselenocysteine [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Selenomethionine (L-selenomethionine, seleno-L-methionine, SeMet, Figure 10, structure 26) is the major selenoamino acid contained in Se-enriched yeasts [3], which has very low toxicity and is non-genotoxic [4,27,101]. Studies have indicated that the tissue accumulation of selenium was better when SeMet was ingested with the diet compared to other forms of selenium [5,27,101].…”
Section: Selenomethioninementioning
confidence: 99%
“…For Se utilization and Se‐protein synthesis, HSe – is phosphorylated by ATP to generate the Se‐donor selenophosphate (SePhp) (Turanov et al., 2011). The pharmacokinetic profiles of Se compounds revealed that SeMet contributed to greater systemic exposure than selenite and MeSeCys (Evans et al., 2019). Administration of SeMet resulted in higher levels of Se deposition in serum, liver, kidney, pancreas, and muscle than administration of selenite and Se‐enriched yeast in broiler breeders (Li et al., 2018).…”
Section: Selenium Species In Cereals and Human Healthmentioning
confidence: 99%
“…The toxicities of Se compounds would be discussed in terms of excessive intake, and certain threshold intake concentrations of different compounds or Se forms need to be further investigated. Administration of 400 μg/day Se in the forms of selenite, MeSeCys, or SeMet for 8 weeks was well‐tolerated and nongenotoxic in cancer patients with chronic lymphocytic leukemia or metastatic solid malignancies (Evans et al., 2019). The excessive intake of Se showed clinical signs of Se toxicity in pigs, and the severity of Se toxicity was presented in the order Astragalus bisulcatus (nonprotein, water‐soluble plant forms of Se, with a small amount of swainsonine causing lesions) > selenate > SeMet (Panter et al., 1996).…”
Section: Selenium Species In Cereals and Human Healthmentioning
confidence: 99%